Sistem Pegambilan Keputusan Bantuan Beasiswa Pendidikan (BAZNAS) Kabupaten Labuhanbatu Berbasis Web - Misbah Rahayu (Universitas Labuhanbatu, 2021)
Baznas (national amil zakat assistance) is an institution that receives, manages, and distributes zakat. Zakat is an obligatory worship that must be performed by a Muslim as we are obliged to perform prayers. according to the religion of Islam, it is a source of funds that can be used to advance the general welfare of the whole community. The Baznas Office of Labuhanbatu Regency, Rantau Utara District, Labuhanbatu Regency is an office that functions in terms of services to the community, students, orphans and others. Every agency or company or organization has a work procedure that is carried out by using this system covering all aspects, both implementation, media, planning to achieving goals.